Self-assembly modification of polyurethane sponge for application in oil/water separation. Issue 69 (5th December 2019) - Liang, Liping; Xue, Yuanyuan; Wu, Qian; Dong, Yanyan; Meng, Xu
Abstract : A polyurethane (PU) sponge with excellent oil/water separation property has been successfully prepared by modifying with octadecyltrichlorosilane (OTS) self-assemblies. Abstract : A polyurethane (PU) sponge with excellent oil/water separation property has been successfully prepared by modifying with octadecyltrichlorosilane (OTS) self-assemblies. The chemical structure, surface topography, and surface wettability of the sponge were characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy, and contact angle experiments, respectively. The prepared sponge could completely absorb oil within a few seconds. In addition, it also possessed excellent selectivity for oil, high absorption capacity (25 times the self-weight), high oil retention (92.6%), and good recyclability. The sponge was synthesized by a facile, mild and inexpensive method, and has excellent potential for use in practical applications because of its desirable property of oil/water separation.